Hydrolutos piaroa sp.n. (Orthoptera: Anostostomatidae), a new semiaquatic Lutosini species from south-western Venezuelan lowland streams - Derka, Tomáš; Svitok, Marek; Fedor, Peter (Zootaxa, 2016)
Hydrolutos piaroa, a new species of Lutosini (Orthoptera: Anostostomatidae) from Tobogán de la Selva (Puerto Ayacucho region, SW Venezuela) is described and figured. Inhabiting aquatic environment it represents an unusual orthopteran with sternal and pleural area covered by fine microtrichia, forming a plastron. This is the first known Hydrolutos species sampled in lowland streams of Venezuelan Guayana.